Nanostructured microporous polymer composite imprinted with superhydrophobic camphor soot, for emphatic oil-water separation - Mishra P.; Balasubramanian K. (My University, 2025)
The pollution of water devastatingly affects the marine environment by physical smothering and intoxication. Therefore, the purification of water resources, especially fresh water reserves, is inevitable in the present age when there is an inadequacy of potable water globally. Due to the ease of access and proficient performance, advanced sorbents are obligatory for the clean-up. Here, we report the oleophilicity of nanostructured superhydrophobic camphor soot particles and their polymer composite, which absorbs oil up to 25 times its own weight. Camphor soot particles exhibit the most consistent reusability after elimination of oil by burning in air, while the microporous composite gives superior absorption characteristics and facile handling. Absence of surface oxidation, barrier-less oleophilicity and faster rate of absorption, together make the material a potentially competent sorbent for oil-water separation. © the Partner Organisations 2014.